2017
DOI: 10.1016/j.jsps.2017.04.040
|View full text |Cite
|
Sign up to set email alerts
|

New chroman-4-one/thiochroman-4-one derivatives as potential anticancer agents

Abstract: The synthesis of 3-[3/4-(2-aryl-2-oxoethoxy)arylidene]chroman/thiochroman-4-one derivatives (-) and evaluation of their anticancer activities were aimed in this work. Final compounds were obtained in multistep synthesis reactions using phenol/thiophenol derivatives as starting materials. For anticancer activity evaluation, all compounds were offered to National Cancer Institute (NCI), USA and selected ones were tested against sixty human tumor cell lines derived from nine neoplastic diseases. The activity resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…For instance, it was found that, in vivo, quercetin exerts a chemo-preventive effect on prostate cancer (reduces the cell viability) by downregulating the activity of pro-proliferative and anti-apoptotic proteins [6]. Additionally, synthetic derivatives of naturally occurring flavonoids (e.g., derivatives of chroman-4-one and tiochromane-4-one [7]) are studied for their anti-cancer properties.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was found that, in vivo, quercetin exerts a chemo-preventive effect on prostate cancer (reduces the cell viability) by downregulating the activity of pro-proliferative and anti-apoptotic proteins [6]. Additionally, synthetic derivatives of naturally occurring flavonoids (e.g., derivatives of chroman-4-one and tiochromane-4-one [7]) are studied for their anti-cancer properties.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 6 was then heated with PPA to obtain the thiochroman‐4‐one derivatives ( 1 ) (Scheme 4). 19 …”
Section: Synthesis Of 2‐(alkyl)thiochroman‐4‐onesmentioning
confidence: 99%
“…Chalcone can be regarded as a privileged structure as it is found in many natural and synthetic compounds featuring a wide range of biological activities, including antimicrobial, antitumor, antioxidant, anti-inflammatory, anticonvulsant, anti-estrogenic and anticancer, etc. 3 The chalcones' decreasing effect on free-radical formation may reduce DNA damage and the risk of mutagenicity. Also, most of the studies reported that chalcones induced apoptosis in the cancer-cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Also, most of the studies reported that chalcones induced apoptosis in the cancer-cell lines. [3][4] This significant substructure possesses a pharmacophoric effect along with anticancer activity described in many studies. [5][6] Although estrogen is primarily known as a reproductive hormone, it also displays many positive effects on the skeleton, cardiovascular and nervous systems.…”
Section: Introductionmentioning
confidence: 99%